Visual Communication in Urban Design and Planning: The Impact of Mediatisation(s) on the Construction of Urban Futures - Gabriela Christmann; Ajit Singh; Jörg Stollmann; Christoph Bernhardt (Urban Planning, 2020)
This editorial introduces the subject matter of the thematic issue, which includes a diverse collection of contributions from authors in various disciplines including, history, architecture, planning, sociology and geography. Within the context of mediatisation processes—and the increased use of ever-expanding I&C technologies—communication has undergone profound changes. As such, this thematic issue will discuss how far (digital) media tools and their social uses in urban design and planning have impacted the visualisation of urban imaginations and how urban futures are thereby communicatively produced. Referring to an approach originating from the media and communication sciences, the authors begin with an outline of the core concepts of mediatisation and digitalisation. They suggest how the term `visualisation' can be conceived and, against this background, based upon the sociological approach of communicative constructivism, a proposal is offered, which diverges from traditional methods of conceptualising visualisations: Instead, it highlights the need for a greater consideration towards the active role of creators (e.g., planners) and recipients (e.g., stakeholders) as well as the distinctive techniques of communication involved (e.g., a specific digital planning tools). The authors in this issue illustrate how communicative construction, particularly the visual construction of urban futures, can be understood, depending upon the kind of social actors as well as the means of communication involved. The editorial concludes with a summary of the main arguments and core results presented.
Keywords: 710; digital tools; mediatisation; urban planning and design; visual communication; visualisations